The Impact of Professional Development Needs on Teachers’ Use of Assistive Technology in Jordanian Special Education Classrooms: Moderating Effects of Age, Education, and Teaching Experience - Alqsairi, Munther Mohammad Qasem; Ab Jalil, Habibah (Advances in Social Sciences Research Journal, 2025)
The effective use of assistive technology (AT) in special education depends largely on teachers’ preparedness and opportunities for professional development (PD). Although PD is intended to enhance teachers’ knowledge and skills, its translation into actual classroom practice remains inconsistent, particularly within the Jordanian context. This study investigates the impact of teachers’ professional development needs on their level of AT use in Jordanian special education classrooms and examines whether age, level of education, and years of teaching experience moderate this relationship. Grounded in the Levels of Use (LoU) dimension of the Concern-Based Adoption Model (CBAM), the study employed a quantitative, cross-sectional survey of 374 special education teachers selected through purposive sampling. Structural equation modeling was used to test the direct and moderate effects. Results revealed a significant positive relationship between professional development needs and teachers’ level of AT use (β = 0.194, p < 0.001), indicating that unmet PD needs strongly predict increased implementation efforts. Moderation findings showed that age, education level, and teaching experience each shaped how PD needs influenced AT use, with significant effects emerging among younger and older teachers, bachelor’s and master’s degree holders, and teachers with low or high experience. These results highlight the importance of differentiated and context-responsive PD programs rather than uniform training approaches. The study provides evidence to guide policymakers, school leaders, and PD designers in developing targeted strategies that improve AT adoption and support equitable learning opportunities for students with disabilities in Jordan.